Vida asociativa presbiteriana: Sociedades femeniles y juveniles durante la primera mitad del siglo XX colombiano - Zambrano Pinargote, Daniel Andrés (Revista Albertus Magnus, 2022)
This article is interested in analyzing two forms of Presbyterian sociability during the first half of the 20th century in Colombia: women's and youth societies. Societies that served as a cultural strategy of this Protestant ecclesial agency for its representation within the religious socio-symbolic space. For this purpose, we will use Maurice Agulhon's sociability category to inquire about the Presbyterian associative life from the mentioned societies, understanding their social incidence and associative work for the identity formation of Colombian Presbyterianism and Protestantism.